Soil-plant spectral technology guiding soil fertility investments in Africa (WLE-ICRAF) - CGIAR Research Program on Water, Land and Ecosystems (2018)
Seventeen African countries are now using soil–plant spectral technology developed by CGIAR Research Program on Water, Land and Ecosystems (WLE) and partners to restore soils and boost agricultural production. The Africa Soil Information Service (AfSIS) is now being deployed for targeting soil fertility restoration strategies. Ethiopia, Ghana, Nigeria, and Tanzania have established state-of-the-art soil information systems based on the technology. NGOs and the private sector are delivering soil testing services to smallholder farmers and monitor intervention impacts on soil health.